Analisis Faktor Makroekonomi yang Berpengaruh terhadap Indeks Harga Saham Gabungan (IHSG) Tahun 2010-2018 - Kurniawati, Ristia; Khairunnisa, Khairunnisa (2020)
In investing, investors and regulators need to do an analysis first. One analysis that needs attention is macroeconomic analysis of the country. Macroeconomic analysis is an analysis relating to economic policies that are influenced by economic conditions in the country. Economic conditions ca be influenced by several factors, including inflation, exchange rates, interest rates, the money supply, and others. The research was conducted to identify the relationship and influence of inflation, exchange rates, interest rates, Gross Domestic Product (GDP), money supply, Dow Jones Industrial Average (DJIA), Strait Times Index (STI), and world oil prices on the Composite Stock Price Index (CSPI) in the period 2010-2018. The data used are secondary data obtained from annual data from 2010-2018. This study uses a saturated sampling method. The number of samples used in this study were 81 sample units. The analytical method used are factor analysis and multiple data regression analysis. Based on factor analysis using the KMO and Bartlett’s test, it was found that the variables that have relationship with the CSPI are the exchange rates variable, Gross Domestic Product (GDP), the money supply, and the Dow Jones Industrial Average (DJIA). Then proceed with multiple regression analysis. Simultaneously the exchange rates, Gross Domestic Product (GDP), the money supply, and the Dow Jones Industrial Average (DJIA) affect of the CSPI. Partially, only the Gross Domestic Product (GDP) has a significant positive effect on the CSPI. Both investors and regulators are advised to take consideration about policies related to Gross Domestic Product (GDP) because it will have an impact on the Composite Stock Price Index (CSPI).